2022
DOI: 10.3390/sym14071308
|View full text |Cite
|
Sign up to set email alerts
|

Complexity Analysis of E-Bayesian Estimation under Type-II Censoring with Application to Organ Transplant Blood Data

Abstract: The E-Bayesian estimation approach has been presented for estimating the parameter and/or reliability characteristics of various models. Several investigations in the literature have considered this method under the assumption that just one parameter is unknown. So, based on Type-II censoring, this study proposes for the first time an effort to use the E-Bayesian estimation approach to estimate the full model parameters as well as certain related functions such as the reliability and hazard rate functions. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…This application is concerned with analyzing a real-world dataset of 56 blood specimens from organ transplant patients. This dataset was originally offered by Hawkins [23] and was then studied by Nassar et al [24]. The organ transplant blood (OTB) data are presented in Table 5.…”
Section: Pathology Data Analysismentioning
confidence: 99%
“…This application is concerned with analyzing a real-world dataset of 56 blood specimens from organ transplant patients. This dataset was originally offered by Hawkins [23] and was then studied by Nassar et al [24]. The organ transplant blood (OTB) data are presented in Table 5.…”
Section: Pathology Data Analysismentioning
confidence: 99%
“…Basheer et al [13] presented hierarchical and E-Bayesian estimations for the inverse Weibull model and concluded that the E-Bayesian was better than the other compared methods. Nassar et al [14] used the E-Bayesian and Bayesian estimation approaches to estimate the generalized inverted exponential distribution parameters under type-II censored data. Mohie El-din et al [15] estimated the parameters of the Gompertz distribution under diferent types of LFs using E-Bayesian estimation.…”
Section: Introductionmentioning
confidence: 99%